Effect of hemicellulose liquid phase on the enzymatic hydrolysis of autohydrolyzed eucalyptus globulus wood - Romaní, Aloia (2012)
In this work, Eucalyptus globulus wood (EGW) was pretreated under autohydrolysis process at 210 and 220 ºC, obtaining a pretreated solid with high cellulose content. Moreover, the effect of the hemicellulosic liquid phase (HLP) addition on the enzymatic hydrolysis was studied. When the enzymatic hydrolysis was performed without addition of HLP, 87.38 and 107.46 g/L of glucose was obtained for 210 ºC and 220 ºC, respectively, showing that the unwashed pretreated solids are susceptible to the enzymatic hydrolysis contributing to reduce operational cost. Additionally, the impact of the inhibitory compounds in the HLP was shown to affect the enzymatic hydrolysis. However, a positive effect was shown on the enzymatic hydrolysis when the xylanases were added using 100 % of HLP, increasing to 35 % and 29 % in the glucose production respect to whole-slurry without addition of xylanases.